(untitled) (Revista Semilleros de Investigación, 2024)
This study conducts a comparative analysis based on the identified characteristics of the loans granted to agricultural production units in the departments of Santander and Norte de Santander according to FINAGRO (2024), considering variables such as the amount disbursed, the term, and the support for the loans by the Agricultural Guarantee Fund (FAG). It identifies a clear divergence in the results of the combination of these variables, with Norte de Santander showing a relative minority in the granting of loans, which coincides with low growth in the agricultural sector over the years, according to the National Agricultural Survey (ENA, 2019).